Dampak Paparan Konten Dakwah @taubatters di Instagram terhadap Tingkat Religiusitas Followers - Jumroni; Karina Aulia Putri (INTERAKSI PERADABAN: Jurnal Komunikasi dan Penyiaran Islam, 2026)
This study aims to determine the effect and the magnitude of the contribution of the intensity of accessing the @taubatters Instagram account on the religious behavior of its followers. The theories utilized include the Stimulus-Organism-Response (S-O-R) Theory, Media Exposure Theory, and the Dimensions of Religiosity. This research employs a quantitative approach using a survey method. By utilizing a purposive sampling technique and Slovin's formula, 100 Generation Z follower respondents (aged 18-28 years) were selected from a total population of 1.3 million. Data collection was carried out by distributing questionnaires via Google Forms, which was then analyzed using simple linear regression with IBM SPSS version 29. The results demonstrate a positive and significant influence of the intensity of accessing the @taubatters account on the followers' religious behavior. This is evidenced by a significance value of < 0.001 and a t-value of 12.056, leading to the rejection of H₀ and the acceptance of H₁. Based on the regression equation Y = 22.973 + 0.925X, the influence is unidirectional. Furthermore, the relationship between the two variables is classified as strong, with a Pearson correlation coefficient of 0.773. The contribution of this influence (coefficient of determination) is 59.7%, while the remaining 40.3% is influenced by other factors outside the scope of this study.